The Global Cost of Inclusive Refugee Education - World Bank (World Bank, Washington, DC, 2021)
This report estimates the cost of educating refugee children in the countries in which they currently reside. The cohort-average annual cost of providing education to all refugee students in low, lower-middle and upper-middle income host countries is 4.85 billion US Dollars. A sensitivityanalysis, relaxing model assumptions, suggests the estimate lies in the range of 4.44 billion and 5.11 billion US Dollars. The total financing envelope required to provide K-12 years of education over a 13-year period to 2032 is 63 billion. As data on the impact of COVID-19’s (coronavirus)impact on education costs and public expenditure is still evolving, this paper provides a pre-COVID-19 baseline for the estimated costs of educating all refugee children. The Global Compact on Refugees (GCR) has placed enhanced responsibility-sharing at the center of the international refugee protection agenda. It commits stakeholders to specific measures to achieve that goal, including a proposal to measure their contributions. Thisrequires a standardized and transparent methodology, developed through a participatory process, that can be used across all host countries; and provides the motivation for this work. The report is cognizant of the fact that education in emergencies is not only a humanitarian crisis but also a development crisis with large numbers of refugee children spending their whole education life cycle in displaced settings. These environments are often already stretched to deliver quality education services. Eighty-five percent of the world’s displaced persons are hosted in low and lower middle-income countries. Where refugees are concentrated in border or rural regions, inclusive education systems can direct resources to previously underserved areas in host countries. Inclusive national education systems promote a streamlined response to the large influx of refugees by building resilient systems with benefits for refugees and host communities alike. It creates a framework for the international community to harmonize efforts and share the collective burden and responsibility of refugee education. The costing methodology developed in this report is based on the key premise that refugee education is embedded in the host country education system, facing the same cost drivers and efficiency and quality constraints. This implies that refugee students receive an education that is "no better, no worse" than host country students in terms of teacher quality, school infrastructure, access to learning materials and other inputs. It starts with the public unit cost of education in each country for each level of education. Refugee education coefficients are then added to the unit costs to provide education services essential to the integration ofrefugees into national systems. These services include accelerated learning programmes, psychosocial support, support in the language of instruction, teacher training in refugee inclusiveness and so on. In addition, given the historical levels of low investment in earlychildhood education (ECE), this paper adds an ECE coefficient to primary public unit costs to estimate pre-primary costs for each country. While this paper uses uniform coefficients acrossall countries, these are likely to vary based on the local context.